Метеорологічні прикмети в народному календарі українців Полісся - Васянович, О. (Народна творчість та етнографія, 2005)
This article gives readers some ideas about Ukrainian folk calendar comparatively to official and church calendars. The role weather in the life of agriculture men through the historical times is being described in it's connection to the biggest Christian holidays. The most important points of folk calendar are being described saporatly.